Psychological Contract Breach and Work Behavior Dynamics with Employee Positive Attitudes as Mediators - Nabila Ardiyanti Nathasya; Fatmah Bagis; Suyoto; Muchammad Agung Miftahuddin (Airlangga Journal of Innovation Management, 2026)
Instability of employment relationships due to Psychological Contract Breach (PCB) in the education sector is a challenge because it can trigger Counterproductive Work Behavior (CWB) and disrupt the quality of learning services, as well as increase the workload of educators and non-educators. This study aims to analyze the influence of PCB on CWB with Organizational Trust (OT) and Work Engagement (WE) as mediating variables in employees. The research used a quantitative approach through Google Forms involving a population of 444 employees, with a final sample of 225 respondents. Data were analyzed using the SEM-PLS method. The results showed that PCB had no effect on CWB, but had an effect on OT and WE. We were shown to have an influence on CWB and were a strong mediator in the relationship between PCB and CWB. This finding supports the Social Exchange Theory (SET) that OT violations lead to a decrease in employee positive attitudes and an increase in the tendency for CWB. The conclusion of this study confirms that WE is a factor in reducing the negative impact of PCBs. Therefore, organizations need to strengthen communication, transparency, fairness, and work support to maintain employee engagement.